Simulation of adsorption processes at metallic interfaces: An image charge augmented QM/MM approach - Golze, Dorothea; Iannuzzi, Marcella; Manh-Thuong Nguyen; Passerone, Daniele; Hutter, Juerg (Journal of Chemical Theory and Computation, 2013)
A novel method for including polarization effects within hybrid quantum mechanics/molecular mechanics (QM/MM) simulations of adsorbate-metal systems is presented. The interactions between adsorbate (QM) and metallic substrate (MM) are described at the MM level of theory. Induction effects are additionally accounted for by applying the image charge formulation. The charge distribution induced within the metallic substrate is modeled by a set of Gaussian charges (image charges) centered at the metal atoms. The image charges and the electrostatic response of the QM potential are determined self-consistently by imposing the constant-potential condition within the metal. The implementation is embedded in a highly efficient Gaussian and plane wave framework and is naturally suited for periodic systems. Even though the electronic properties of the metallic substrate are not taken into account explicitly, the augmented QM/MM scheme can reproduce characteristic polarization effects of the adsorbate. The method is assessed through the investigation of structural and electronic properties of benzene, nitrobenzene, thymine, and guanine on Au(111). The study of small water clusters adsorbed on Pt(111) is also reported in order to demonstrate that the approach provides a sizable correction of the MM-based interactions between adsorbate and substrate. Large-scale molecular dynamics (MD) simulations of a water film in contact with a Pt(111) surface show that the method is suitable for simulations of liquid/metal interfaces at reduced computational cost. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20